Integrating omics reveals that miRNA-guided genetic regulation on plant hormone level and defense response pathways shape resistance to Cladosporium fulvum in the tomato Cf-10-gene-carrying line - Liu, Guan; Liu, Fengjiao; Zhang, Dongye; Zhao, Tingting; Yang, Huanhuan; Jiang, Jingbin; Li, Jingfu; Zhang, He; Xu, Xiangyang (Frontiers in Genetics, 2023)
Invasion of Cladosporium fulvum causes the most serious diseases affecting the reproduction of tomatoes. Cf-10 gene carrying line showed remarkable resistance to C. fulvum. To exploit its defense response mechanism, we performed a multiple-omics profiling of Cf-10-carrying line and a susceptible line without carrying any resistance genes at control and 3 days postinoculation (dpi) of C. fulvum. We detected 54 differentially expressed miRNAs (DE-miRNAs) between the control and 3 dpi in the Cf-10-carrying line, which potentially regulated plant-pathogen interaction pathways and hormone signaling pathways. We also revealed 1,100 differentially expressed genes (DEGs) between the control and 3 dpi in the Cf-10-carrying line whose functions enriched in pathways that were potentially regulated by the DE-miRNAs. Integrating DE-miRNAs, gene expression and plant-hormone metabolites indicated a regulation network where the down-regulation of miRNAs at 3 dpi activated crucial resistance genes to trigger host hypersensitive cell death, improved hormone levels and upregulated the receptors/critical responsive transcription factors (TFs) of plant hormones, to shape immunity to the pathogen. Notably, our transcriptome, miRNA and hormone metabolites profiling and qPCR analysis suggested that that the downregulation of miR9472 potentially upregulate the expression of SAR Deficient 1 (SARD1), a key regulator for ICS1 (Isochorismate Synthase 1) induction and salicylic acid (SA) synthesis, to improve the level of SA in the Cf-10-carrying line. Our results exploited potential regulatory network and new pathways underlying the resistance to C. fulvum in Cf-10 gene carrying line, providing a more comprehensive genetic circuit and valuable gene targets for modulating resistance to the virus.